PENGARUH KOMPOS LIMBAH SAYUR-SAYURAN TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora Pierre) - Citra Y Siallagan; Tengku Nurhidayah; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to study the effect and to obtain the best dose of vegetables waste compost on the growth of coffee Robusta seedlings. The experiment has been conducted at the Experimental Farm of the Faculty of Agriculture, Riau University from May to August 2016. The experimental unit was arranged in a Completely Randomized Design, consisting of 5 treatments and 4 replications. The treatments consisted of the dose of vegetables waste compost, a.i : 0 g, 40 g, 80 g, 120 g and 160 g/seedling. Parameters observed were plant height increment, number of leaves increment, increase of stem diameter, leaf area and root volume. Data were analyzed using analysis of variance and the mean of each treatment was compared with Duncan’s New Multiple Range Test at 5 % level. The result showed that the dose of vegetables waste compost at 120 g/seedling 160 g/seedling gave a better effect on enhancing the growth of coffee Robusta seedling. Keywords : Coffea canephora Pierre, vegetables waste compost dose